Developing Nias Culture-Based English Textbook to Enrich 21st Century Skills for Vocational High School Students - Mercy Dwiyul Halawa; Yasminar Amaerita Telaumbanua; Adieli Laoli; Trisman Harefa (Universitas Tidar, 2025)
This study focuses on the development of a Nias culture-based English textbook designed to enrich 21st century skills in vocational high school students. The problem underlying this study is the low relevance of the teaching materials used to the local cultural context making it difficult for them to understand the material in depth. Using a Research and Development (R&D) approach with the ADDIE model, the textbook was designed, developed, implemented, and evaluated in terms of feasibility, practicality, and effectiveness. The effectiveness of the product is tested using a quasi-experimental method with a nonequivalent control group posttest-only design. The research sample was determined using cluster sampling to represent students in different class groups. Research subjects included an experimental class, control class and an additional school as the dissemination class. Data is collected through expert validation, implementation, questionnaires, and learning outcome tests. The validation results showed high feasibility scores from four experts (100% culture and material, 95.55% language, 85.71% design). The developed book was also found to be practical and effective in enhancing students’ 21st-century skills, particularly in communication, collaboration, critical thinking, and creativity. The posttest results revealed clear improvements in students’ learning outcomes compared to the control class. Moreover, both teachers and students responded positively, emphasizing the textbook’s relevance to local culture and its usefulness in the learning process. Therefore, the Nias culture-based English textbook can be concluded as a feasible, practical, and effective learning resource that integrates local wisdom, strengthens students’ cultural identity, and fosters essential 21st-century competencies.